Pengaruh Fasilitas Belajar terhadap Hasil Belajar Siswa Kelas VII-11 SMP Negeri 1 Setu Bekasi Jawa Barat - Yosita Apriliasari; Boma Jonaldy Tanjung (Arden Jaya Publisher, 2022)
This study aims to determine how the influence of learning facilities on student learning outcomes in class VII-11 SMP NEGERI 1 Setu Bekasi, West Java. This type of research is quantitative research with a correlational approach. Sampling was done using simple random sampling technique with a total of 40 students. With data collection techniques through questionnaires (questionnaires), report cards and documentation. Data collection techniques used in this study were observation, questionnaires and document analysis. The process of developing job satisfaction instruments begins with the preparation of an instrument in the form of a questionnaire using a Likert scale with validity and reliability tests. For technical data analysis using descriptive analysis and prerequisite tests which include normality test and linearity test. The hypothesis test uses t test (partial test). Based on data analysis, it was concluded that there was no influence of learning facilities on student learning outcomes. Based on the calculation results, it is shown through the results of the t-test (partial) indicated by the results of the t-count calculations which show a value of 2.369, according to the table above. T table is 2.026 proves that t count exceeds t table. A significant value (Sig.) of 0.023, or less than 0.05, was achieved for the partial test using Sig (alpha 5 percent). This shows that the variable learning facilities do not have a diverse influence on student learning outcomes.